Persepsi Guru Terhadap Implementasi Kurikulum Merdeka Belajar di SMP Swasta Hanura Danga - Maria Kristina Ota; Helena Rosalia Parera; Wilhelmina Nau (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2024)
This research aims to determine: (1) Teachers' perceptions of the independent learning curriculum at Hanura Danga Private Middle School; (2) Implementation of the independent learning curriculum at Hanura Danga Private Middle School.The type of research is combination research (Mix Methods), this type of research uses quantitative methods and qualitative methods and data collection techniques (1) Questionnaires, (2) Interviews, (3) Documentation. The data collected is analyzed using Percentage Descriptive Statistics analysis.Based on the results of data analysis and discussion to prove the research findings; (1) Teachers' perceptions of the independent curriculum as a whole, teachers have very good positive perceptions of the Independent Learning Curriculum. Analysis of questionnaire data distributed to 24 teachers shows a very high level of acceptance of the Independent Learning Curriculum, namely 96%, (2) Interview results to find out how the curriculum is implemented at Hanura Danga Private Middle School, the interview results confirm these findings, with the majority of teachers providing positive feedback on the implementation of the curriculum at Hanura Danga Private Middle School. Thus it can be suggested; (1) For schools to prepare facilities provided by the school such as providing regular training or technical guidance, providing adequate resources, and providing adequate support from school principals, it is necessary to maintain them, because this is what is needed to facilitate teachers in the successful implementation of the independent curriculum. (2) Educators can take advantage of the freedom provided by the Independent Curriculum in designing and compiling learning materials that are more contextual and relevant to students' needs. Apart from that, educators can also pay attention to factors that influence the implementation of the Merdeka Curriculum in each subject), such as the availability of resources and support from school principals. (3) For further researchers, teachers can compare perceptions of the Merdeka Curriculum with the curriculum previously implemented in school